Delayed diagnosis of a flexion-distraction spinal injury and occult small bowel injury in a pediatric trauma patient: Importance of recognizing the abdominal “seatbelt sign” - Henry, Derrick A. (Trauma Case Rep, 2021)
Spine trauma in the pediatric population can present with occult spinal and visceral injuries, presenting unique diagnostic challenges. Subtle imaging findings, as well as difficulty in patient participation with history and examination can contribute to a delayed or missed diagnosis. This in turn can be detrimental to recovery, leading to significant delay in care, additional morbidity, and cost. We present the case of an 11-year-old female patient with a delayed diagnosis of an unstable three-column lumbar spine injury as well as an occult small bowel injury that evaded diagnosis despite multiple hospitalizations and a plethora of imaging and treatment modalities. This led to several extended hospital stays and numerous interventions and surgeries to treat her injuries. We present this case to highlight the sequela of such an injury, and to broaden awareness across specialties of an injury pattern which requires a heightened index of suspicion to detect.